Submental intubation in oral maxillofacial surgery (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Oral and maxillofacial surgical procedures present a unique set of problems for both the anaesthesists and the surgeons. Simultaneous access to the oral or nasal cavities and dental occlusion is required for the surgical treatment of some craniofacial deformities. Generally, airway is maintained by orotracheal or nasotracheal intubation and some instances by tracheostomy however, nasotracheal intubation is contraindicated in skull base or midface fracture. Tracheostomy has inherent complications ranging from surgical emphysema to disfiguration where as orotracheal route prevents free access to oral cavity. In these circumstances, submento-tracheal intubation may provide a better option to overcome these problems.Objective: The aim of this study was to evaluate outcome of conversion of orotracheal route to submentotracheal route for surgical correction of maxillofacial trauma & deformity and time required to change from oral to submental route, accidental extubation, postoperative complications, and the healing of intraoral and submental scars were evaluated.Patients and Methods:Method: A total of 23 patients were selected from maxillofacial department of BSMMU and other institutions from December 2007 to March 2011 to use this technique. After standard orotracheal intubation, a 2 cm incision was made lateral to the midline in the submentum and a blunt dissection opposite to the skin incision on the lingual aspect of the mandible provides access to the floor of the mouth, the orotracheal tube is disconnected and pulled through the floor of the mouth then to the submental incision, the tube is then sutured to the skin. Surgery was completed without interference from flexometallic endotracheal tube. Following surgery the sequence is reversed and the patients extubated in the conventional manner.Results The technique was used in 13 patients with multiple facial fractures & 10 patients with facial deformity. The mean age of the group was 30 (20-50) years .The submental orotracheal intubation was completed successfully in all patients. No accidental extubations or tube injuries occurred. The mean time required for intubation was 6 minutes. All patients were extubated in the operating theatre. The intraoral and submental accesses healed with minimal scarring in all patients .There were no incidence of intra- or postoperative complications related to submental intubation.Conclusions Submental intubation is a simple, safe, and predictable approach without significant morbidity that facilated safe airway and enhances meticulous surgical procedure of fractured skull base and midface.JBSA 2012; 25(1): 21-27